2005
DOI: 10.1097/01.ccm.0000162565.18193.e5
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine does not improve patient satisfaction when compared with propofol during mechanical ventilation*

Abstract: Despite theoretical advantages of DEX to improve overall patient satisfaction, the two agents provide similar responses to amnesia and pain control. According to our findings, DEX does not seem to have any advantage compared with propofol for short-term sedation after coronary artery bypass graft surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
139
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 26 publications
1
139
1
1
Order By: Relevance
“…) than in most previous studies [10][11][12]. A need for additional sedatives has been reported with dexmedetomidine at doses of up to 2.5 lg kg -1 h -1 [13].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…) than in most previous studies [10][11][12]. A need for additional sedatives has been reported with dexmedetomidine at doses of up to 2.5 lg kg -1 h -1 [13].…”
Section: Discussionmentioning
confidence: 71%
“…Dexmedetomidine was associated with less coma (defined as RASS -4 to -5) and markedly increased fentanyl needs in patients with RASS target -3 or deeper [14]. When viewed together with its short-term use [6,10,11] and any long-term use [12][13][14], our results suggest that dexmedetomidine should be further assessed for mild to moderate sedation rather than as sole sedative for deep sedation. Use of sedation protocols with daily sedation stops and sedation scores has been able to reduce the duration of mechanical ventilation and intensive care [1,2].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…One study was available to inform the hypothesis; in 89 surgical ICU patients receiving mechanical ventilation, propofol and dexmedetomidine provided equivalent amnesia and pain control, but dexmedetomidine led to greater discomfort and sleeping difficulties [30]. The present study compared patient comfort among sedatives using MMTA.…”
Section: Original Researchmentioning
confidence: 93%
“…Similar findings were referred to in a metaanalysis by Lynn and others [39] analysing the safety and efficiency of dexmedetomidine with post-operative cardio-surgical patients. Numerous studies comparing dexmedetomidine to propofol [40,41], midazolam [40,42,43], and morphine [44] confirmed that dexmedetomidine reduces the risk of delirium, agitation and/or confusion in critical ICU patients. This medicine is not yet registered in Serbia.…”
Section: Discussionmentioning
confidence: 99%